A Turn‐On Fluorescent Probe for Highly Selective and Sensitive Detection of Palladium. Issue 7 (19th May 2016) - Zhou, Junliang; Zhang, Jian; Ren, Hang; Dong, Xiaochun; Zheng, Xing; Zhao, Weili
Abstract: A novel turn‐on fluorescent probe for the detection of palladium has been designed. The probe can selectively and sensitively detect palladium in solution, and the limit of detection was calculated to be 11.4 nmol·L −1 . Furthermore, the probe was successfully used for fluorescence imaging of palladium in living cells. Abstract : A novel turn‐on fluorescent probe for the detection of palladium has been designed. The probe can selectively and sensitively detect palladium in solution, and the limit of detection was calculated to be 11.4 nmol·L −1 . Furthermore, the probe was successfully used for fluorescence imaging of palladium in living cells.